THE PREDOMINANT EDUCATIONAL PHILOSOPHIES AMONG PRE-SERVICE ENGLISH TEACHERS - Indaswari, Ragilia; Ena, Ouda Teda (University of Kuningan, 2025)
Theory and philosophy are inseparably linked. Theory shapes how people purposefully engage with the world, whereas philosophy shapes how people perceive the world. The idea behind this study is that pre-service English teachers follow certain beliefs to improve their pedagogical abilities prior to the implementation. This study investigated the predominant educational philosophies among pre-service English teachers enrolled in an English Education program at a University in Solo. The respondents of the study were 38 pre-service English teachers at a University in Solo, Central Java who were chosen through simple random sampling. Data were collected using a survey adapted from the self-assessment educational philosophies scoring guide. It utilized a quantitative survey research that involves gathering data through questionnaires. The analysis revealed that Behaviorism emerged as the most commonly endorsed philosophy, followed by Perennialism and Progressivism. These findings suggest that pre-service English teachers tend to adopt teacher-centered approaches that emphasize structure, repetition and reinforcement. The study suggests that Indonesian pre-service English teachers believe effective teaching involves a combination of student-centered and teacher-centered approaches, urging for curriculum support.